Oh what a paradise it seems - Cheever, John. (New York : Vintage Books, 1991)
Lemuel Sears is an elderly romantic who falls in love with strangers of both sexes and struggles to save a pond from polluters.
Originally published: New York : Knopf, 1982.
Adult
Keywords: Environmentalists -- Fiction; Older men -- Fiction; Elderly men -- Fiction; Environmentalists -- Fiction